Reconocemos patrones gráficos y numéricos - Romero Reyes, Bartolomé Jorge (2019)
The present work of professional sufficiency entitled "We recognize graphic and numerical patterns", aimed at students of the fifth Grade of Primary Education, of I.E No. 80014 "Juan Pablo II" of the city of Trujillo in the year 2019._x000D_ The present work consists of the development of a learning session in the area of mathematics taking into account the problem-solving approach, for the achievement of the competence Solves problems of regularity, equivalence and Change, making use of a series of own abilities of the competition described above being this: Use strategies and procedures to find general rules, which will allow you to put into play higher order skills such as reasoning and creativity._x000D_ All the development of the session has been designed according to the achievement of the performance: It makes statements about the non-immediate elements that continue a pattern. He justifies them with examples, simple calculations and properties of equality or his knowledge. That it will be evident when students find the law of formation that meets a graphic pattern and expresses it mathematically._x000D_ It also has the development of the thematic field embodied in the theoretical support that allows us to expand our knowledge about the subject while describing the pedagogical and didactic processes that have been followed throughout the process detailing the strategies that have been used in each of these processes